MultiParameter Fiber-Optic Sensor for Simultaneous Measurement of Thermal Conductivity, Pressure, Refractive Index, and Temperature - Simon Pevec; Denis Donlagic (IEEE Photonics Journal, 2017)
This paper presents a miniature, all-silica four/multiparameter sensor for simultaneous measurements of thermal conductivity, pressure, refractive index, and temperature of gases. The sensor is composed of multiple Fabry–Perot interferometers (FPIs) that were created at the tip of a standard optical fiber by a micromachining process based on selective etching and standard fiber manipulation steps. The experimental sensor length was below ${\rm{3.4\,mm}}$ , while the diameter did not exceed $125\,μ {\rm{m}}$ . Interrogation of the sensor utilized acquisition and appropriate signal processing of the back-reflected optical spectrum, which allowed for crosstalk free extraction of individual resonators’ lengths. High repeatability and resolutions were demonstrated for all four sensed parameters. The sensor might be applied to a variety of problems related to gas monitoring or composition analyze as, for example, binary, or even trinary gas mixtures.